Importance of accurate ilio-inguinal quantification in lower extremity lymphoscintigraphy. Issue 3 (March 2017) - Keramida, Georgia; Winterman, Nicola; Wroe, Emma; Aplin, Mark; Peters, A. Michael
Abstract : Aims: The aims of this study were to improve the quantification of lower extremity lymphoscintigraphy, determine its value and lower limit of normal, and determine whether intermediate postinjection time imaging is necessary. Patients and methods: This was a study of 102 consecutive patients undergoing routine lower extremity lymphoscintigraphy using subcutaneous 99m Tc-99m-nanocolloid with imaging at 5, 45 and 150 min after injection. Abnormal imaging criteria were delay (no activity in ilio-inguinal nodes at 45 min or negligible activity at 150 min), lymph diversion (through skin or deep system) and focal accumulation suggesting cellulitis. Lymphatic function was quantified as % injected activity in ilio-inguinal nodes at 150 min (IIQ) using a standard placed, by image guidance, exactly over the nodes. Results: Forty-one patients had bilateral normal scintigraphy. IIQ was normally distributed in 15 limbs, with IIQ of 1–7.5%. In contrast, it was log-normally distributed in 68 limbs, with IIQ of at least 7.5%, suggesting 8% as the lower limit of normal. In 57 limbs, delay was the only scintigraphic abnormality at 45 min. Of these, 33 were abnormal at 150 min. Of the remaining 24 limbs, 17 had reduced IIQ; thus, 50 of these 57 (88%) limbs had lymphatic dysfunction. The seven limbs that remained normal at 150 min were in six patients. The contralateral limb was abnormal in five of these six patients; hence, lymphatic dysfunction would have been missed in only one patient without 45 min imaging. Conclusion: IIQ is strongly recommended. Isolated delay at 45 min is abnormal. However, 45 min imaging is not necessary if IIQ is performed.